Tourism resources and landscape heritage at the sites. Venezuelan experience - Boada, Ceres Isabel (2023)
The cultural and natural landscape heritage can serve as the foundation for tourism and is a non-renewable resource that must be planned for, or it could be altered. Sustainable tourism is a requirement for long-term development and benefits both the tourist destination and the host community in social, economic, and environmental terms. Moving from landscape heritage to tourism products requires planning and management. The integrated geotourism approach represents a feasible choice for sustainable tourism. It involves the most significant amount of heritage assets from the geographic characteristics of a place. This approach creates a sense of commitment to the community, along with social equity, environmental balance, human development, and quality of life for future generations, and contributes to the promotion of heritage assets. This approach is the initial step in determining the tourism potential of three sites in Merida, Venezuela, with a rich heritage, ideally suited for promoting sustainable local development following the planning process.